Hubungan Komunikasi Dan Kepemimpinan Terhadap Kinerja Pengawai Kantor Sistem Administrasi Manunggal Satu Atap Kabupaten Bireuen - Khairani, Cut; Muttaqim, Hakim (Fakultas Ekonomi Universitas Almuslim Bireuen, 2021)
The aim of this research is to determine and analyze the influence of communication and leadership on employee performance at SAMSAT Bireuen. The research involved all office employees, namely 40 people. The research uses survey methods and questionnaires as data collection techniques for analysis using regression and correlation procedures. From the research results, it was found that communication and leadership variables had a positive influence on the performance of SAMSAT Bireuen office employees